Optimalisasi Manajemen Agribisnis dalam Peningkatan Produktivitas Pertanian Berkelanjutan - lusia astuti; Billi Rifa Kusumah; Nurul Ekawati; Teni Novianti (LPPM UNU CIREBON, 2025)
Sustainable agriculture is a strategic approach that combines high productivity with the preservation of natural resources. In this context, agribusiness management plays a key role in increasing the efficiency and effectiveness of agricultural production. The aim of this research is to discuss various agribusiness management strategies that can be implemented to support increased sustainable agricultural productivity. The main focus includes resource management, technology application, business diversification, and farmer capacity development. This type of research is qualitative with the research location in West Java. The research subjects consisted of farmers, agribusiness managers, agricultural extension workers, and agricultural experts who had experience and knowledge in the field of agribusiness. Data collection techniques use interviews, observation and documentation. The results of this research are that optimizing agribusiness management through efficient resource management, application of technology, business diversification, marketing strategies and farmer capacity development can increase productivity and sustainability of the agricultural sector. Support from multiple stakeholders is critical to expanding adoption of these practices. This research recommends increasing farmers' access to technology, training and markets to support the transition to more productive sustainable agriculture.